Phosphate recovery from the P-enriched brine of AnMBR-RO-IE treating municipal wastewater via an innovated phosphorus recovery batch reactor with nano-sorbents - Zhao, Qian (2022)
Municipal wastewater is a very unique pool full of energy and useful substances. Though the innovative integrated anaerobic membrane bioreactor and reverse osmosis-ion exchange (AnMBR-RO-IE) process can produce high-grade reclaimed water with high energy efficiency, phosphorus resources recovery in the WWTPs has been rarely reported thus far. This study evaluated the feasibility of a phosphorus recovery batch reactor (PRBR) as an approach for the phosphate production from the P-enriched brine from AnMBR-RO-IE. With operating PRBR for 162 cycles, high to 85% of P recovery rate was obtained for 145 cycles, leading to a P production rate of 6.17 g/m3 domestic wastewater with nano-sorbents (NSs) consumption rate of 10.2 g/m3. Acidification pretreatment efficiently improved the adsorption capacity and reduced the NSs renewing frequency. High adsorption selectivity of NSs contributed to low impurities (<0.3%) in the P-enriched reclaimed solution. Moreover, the integrated AnMBR-RO-IE-PRBR process saved 47% of energy consumption compared to the present NEWater production process in Singapore. The innovative PRBR reactor was competitive compared to the commonly-used chemical precipitation methods in conventional WWTPs in terms of phosphorus recovery/loss and energy balance. It is expected that the proposed integrated process can offer new insights into the direction of phosphorus reclamation in the future WWTPs.